Modelo de conservação da área de proteção ambiental do Baixo Rio Pacoti, Ceará - Ávila, Francisco José Capibaribe (2005)
The hydrographic basin of the Pacoti River is the major source of water for the city of Fortaleza and is of major importance to the fundamental ecosystems of the region. It is also important for the maintenance of coastal dynamic processes and the life quality of the surrounding communities. The protected environment area of the lower part of the Pacoti River covers different areas including mangroves, sand dunes and “tabuleiro, ciliar and várzea” vegetation. The irregular areas of human occupation in these areas, especially of permanent preserved areas is threatening the integrity and functionality of the system as well as the biodiversity. There is an urgent need of a means of controlling these harmful activities and punishing the people involved. Since this area of preservation does not yet have a management plan established, it is still unprotected and subjected to constant invasions and degrading activities such as mining, forest clearing, irregular construction and pollution of its tributaries. This study suggests the environmental legislation should be enforced through the formation of a management committee including representatives of the managing bodies, the land owners and members of the community. This committee is going to be a means of enabling the preservation of the area, by enforcing the environmental laws, recovery of damaged areas, developing programs of environmental education in order to allow sustainable development to take place.